Utilization of Kine Master Application as a Learning Video - Erwin, Erwin; Japakiya, Rusdee; Saputra, Dedi (International Journal of Language and Ubiquitous Learning, 2023)
Background. The subject of natural science at the level of elementary school education grade 3 semester 1 is to learn about living things. Purpose. The purpose of this article is to find out what methods or media are suitable for students during the Covid-19 pandemic. Then the technology that can be utilized in the learning process so that educators and students can still meet virtually during the learning process Method. The technique used in this investigation is an approximation technique by surveying the school before the online teaching process is carried out with the aim of seeing what kind of methods and media are used by educators at the elementary school. Results. In the first part, it can be recapitulated that 90% of learners cannot understand the learning provided through WhatSapp Group. In the second part, it can be recapitulated that 96% of students can understand the learning well, the learning process takes place through the Zoom Meeting application by displaying learning media in the form of videos created and edited using the KineMaster application. 4% of the learners experienced problems during the learning process. They are constrained by the network and do not have a HandPhone so that the video displayed during learning in the Zoom Meeting is sent back to the WhatSapp Group of class 3. Conclusion. Kine master app can be used during online learning with the help of zoom app or other learning video apps.